A review on simulation based training on autonomous ships and protection of Egyptian maritime security - Ashraf Mohamed Elsayed (Maritime Research and Technology, 2023)
Abstract Autonomous ships are gaining more and more favor in the maritime sector as a result of their ability to boost productivity while simultaneously lowering costs and boosting levels of safety. However, the proliferation of autonomous ships brings with it new worries about cybercrime, piracy, and other challenges to maritime safety and security. Protecting marine security is of the highest significance in Egypt since the Suez Canal is an essential transportation route for international business. This research study investigates the function that training plays in improving both the general security of autonomous ships that operate in Egyptian seas as well as the cyber security of such ships. This research summarizes the findings of a survey of Egyptian maritime stakeholders about their perspectives of the necessity and efficacy of training for autonomous ships. The survey asked respondents about the available literature on training for autonomous ships and maritime security. The paper also evaluates this literature. According to the findings of the research, even though there is a rising knowledge of the significance of training for autonomous ships, there are substantial gaps in training programs and resources in Egypt. This is despite the fact that there is a growing awareness of the value of training for autonomous ships. The findings of the research are summarized in a set of suggestions for boosting Egypt's marine security and the quality of its training programs.   Received: 19 June 2023 Accepted: 22 August 2023 Published: 05 December 2023